2019
DOI: 10.3390/su11092473
|View full text |Cite
|
Sign up to set email alerts
|

For Sustainable Benefits and Legacies of Mega-Events: A Case Study of the 2018 PyeongChang Winter Olympics from the Perspective of the Volunteer Co-Creators

Abstract: This study examined the outcome of the 2018 PyeongChang Winter Olympics from multiple perspectives. Tourism and sport researchers have focused on the legacy of mega-events, due to the opportunity they provide to transform a city positively, including through the development of the tourism industry. However, outcomes are not always positive, and the effects differ for every event. The effects of an event can be short-term or long-term. An event, to be truly successful, should aim to have a long-lasting and sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 52 publications
0
20
0
4
Order By: Relevance
“…Mega events, especially sports extravaganzas, have been a popular research area owing to their power in initiating various transformative changes in host cities, communities, and countries (Preuss, 2015). Higher tourist arrivals and tourism receipts, increased destination awareness, enhanced host image, higher likelihood of repeat visits, improved infrastructure, local pride, and more employment opportunities have been cited among the tourism-related benefits of mega events (Getz and Page, 2016; Kim et al, 2019; Walker et al, 2013). These benefits largely motivate countries and cities to seek opportunities to host mega sports events (Kim et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Mega events, especially sports extravaganzas, have been a popular research area owing to their power in initiating various transformative changes in host cities, communities, and countries (Preuss, 2015). Higher tourist arrivals and tourism receipts, increased destination awareness, enhanced host image, higher likelihood of repeat visits, improved infrastructure, local pride, and more employment opportunities have been cited among the tourism-related benefits of mega events (Getz and Page, 2016; Kim et al, 2019; Walker et al, 2013). These benefits largely motivate countries and cities to seek opportunities to host mega sports events (Kim et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such media coverage made the host city less desirable to potential visitors. Furthermore, the host country and the specific host city of its mega event may differ vis-à-vis associated attitudes and visit intention (Kim et al, 2019; Minnaert, 2012). For this reason, researchers have investigated mega events multi-contextually.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of increasing awareness, South Korea has hosted three international-scale mega events: the 1988 Seoul Summer Olympics, the 2002 FIFA World Cup, and the 2018 PyeongChang Winter Olympics. The successful hosting of the 2018 PyeongChang Winter Olympics showed that investing to bid and host Olympic events can be financially beneficial with a low budget and a high efficiency, even though other recent Olympics have been financial disasters [28]. These mega events helped place South Korea on the world tourism market.…”
Section: Contextual Setting: Overview Of Tourism In South Koreamentioning
confidence: 99%
“…Other subjects considered are buildings [121][122][123][124], business [125], education [126], climate [127], and organization [128][129][130]. One last trend to consider in the studies is the role, expectation, and importance of volunteering in the success of the SMEs, specifically in the OG [131,132].…”
Section: Analysis Of the Literature On Sme And Sustainabilitymentioning
confidence: 99%